Gr-1+ Cells Other Than Ly6G+ Neutrophils Limit Virus Replication and Promote Myocardial Inflammation and Fibrosis Following Coxsackievirus B3 Infection of Mice - Xu, Dan; Wang, Peijie; Yang, Jie; Qian, Qian; Li, Min; Wei, Lin; Xu, Wei (Frontiers in Cellular and Infection Microbiology, 2018)
Coxsackievirus B3 (CVB3) is the primary cause of viral myocarditis. An early and abundant neutrophil accumulation in the myocardium is a hallmark of early CVB3 infection. Yet the relative contribution of neutrophils to host susceptibility to CVB3 myocarditis remains largely unknown. Herein, peripheral neutrophil depletion was implemented in a BALB/c mouse model of acute CVB3 myocarditis using the specific 1A-8 (anti-Ly6G) or a RB6-8C5 (anti-Gr-1) mAb covering a wide range. Anti-Ly6G treatment led to systemic neutropenia throughout the disease, but did not alter virus replication, disease susceptibility and histopathological changes in the heart and pancreas of mice. In contrast, depletion of both neutrophils and monocytes/macrophages by anti-Gr-1 mAb prior to and after infection significantly promoted susceptibility of mice to CVB3 infection which was associated with exacerbated cardiac and pancreatic viral load. However, depletion of Gr1+ cells significantly suppressed acute myocarditis and pancreatic acini destruction at day 7 post infection via reducing Ly6Chigh monocyte population in the circulation. Additionally, cardiac interstitial fibrosis was not affected by neutrophil depletion, whereas Gr-1+ cells other than neutrophils increased cardiac fibrosis at day 21 p.i. by increasing cardiac expression of profibrotic cytokine TNF-α and TGF-β. Thus, Neutrophil function is most likely not essential for CVB3 control and peripheral neutrophils play dispensable role in the pathogenesis of acute myocarditis and pancreatitis during CVB3 infection. Whereas Gr-1+ cells other than neutrophils play a major role in limiting viral replication while promoting myocardial and pancreatic inflammatory injury and fibrosis.